A is for asylum seeker : words for people on the move = A de asilo : palabras para personas en movimiento - Buff, Rachel, 1961- (Fordham University Press, 2020)
A clear and concise A-to-Z of keywords that echo our current human rights crisisAs millions are forced to leave their nations of origin as a result of political, economic, and environmental peril, rising racism and xenophobia have led to increasingly harsh policies. A mass-mediated political circus obscures both histories of migration and longstanding definitions of words for people on the move, fomenting widespread linguistic confusion. Under this circus tent, there is no regard for history, legal advocacy, or jurisprudence. Yet in a world where the differences between "undocumented migrant" and "asylum seeker" can mean life or death, words have weighty consequences. A timely antidote to this circus, A is for Asylum Seeker reframes key words that describe people on the move. Written to correct the de-meaning of terms by rhetoric and policies based on dehumanization and profitable incarceration, this glossary provides an intersectional and historically grounded consideration of the words deployed in enflamed debate. Skipping some letters of the alphabet while repeating others, thirty terms cover everything from Asylum-seeker to Zero Tolerance Policy. Each entry begins with a contemporary or historical story for illustration and then proceeds to discuss the language politics of the word. The book balances terms affected by current political debates--such as "migrant," "refugee," and "illegal alien"--And terms that offer historical context to these controversies, such as "fugitive," "unhoused," and "vagrant."Rendered in both English and Spanish, this book offers a unique perspective on the journeys, histories, challenges, and aspirations of people on the move. Enhancing the book's utility as an educational and organizing resource, the author provides a list of works for further reading as well as a directory of immigration-advocacy organizations throughout the United States.*****Un claro y breve abecedario de palabras clave que hacen eco en nuestra crisis humanitaria presente. Mientras millones son forzados de huir de sus naciones de origen debido a peligro político, económico, y ecológico, racismo y xenofobia han llevado a políticas más y más severas. Un circo político en los medios oculta a ambas las historias de inmigración y las definiciones antiguas de palabras para personas en movimiento, creando confusión lingüística amplia. Bajo esta carpa de circo, no hay consideración para historia, defensa legal, o jurisprudencia. Pero en un mundo donde las diferencias entre "migrante indocumentade" y "solicitante de asilo" pueden ser la diferencia entre vida y muerte, palabras tienen consecuencias graves. Un antídoto oportuno a este circo, A de Asilo re-enmarca palabras claves que describen a personas en movimiento. Escrito para corregir la de-significación de términos por retórica y políticas basadas en deshumanización y encarcelación lucrosa, este glosario provee una consideración interseccional e histórica de las palabras usadas en debate inflamado. Brincando a unas letras del alfabeto mientras repite a otras, treinta términos cubren todo desde Asilo a Tolerancia Cero. Cada artículo empieza con una historia contemporánea u histórica para ilustrar, y después discute la política alrededor de la palabra. El libro balancea términos impactados por debates políticos contemporáneos--como "migrante," "refugiado" y "extranjero ilegal"--y términos que ofrecen contexto histórico a estas controversias, como "fugitivo" "sin casa" y "vagante."Escrito en inglés y español, este libro ofrece una perspectiva única en las jornadas, historias, retos, y aspiraciones de personas en movimiento. Aumentando la utilidad del libro como un recurso educacional y organizacional, la autora provee una lista de obras para más lectura, igual que un directorio de organizaciones de defensa de inmigrantes a través de los Estados Unidos